Pengawasan Peredaran Kosmetik Ilegal Oleh BPOM Di Gorontalo - Karmila Mokodongan; Rafika Nur; Asdar Arti (International Forum of Researchers and Lecturers, 2023)
The objective taken by the researchers was to find out what the BPOM's obstacles were in controlling the distribution of illegal cosmetics in Gorontalo City, one of the efforts made by the government to improve public health and carry out supervision by forming BPOM. Cosmetic products that do not have distribution permits or are illegal which do not comply with applicable regulations are still a problem for the people of Gorontalo. This can be seen from the existence of cosmetic distribution facilities that sell illegal cosmetics that have not been controlled by BPOM in Gorontalo City. This study uses an empirical juridical legal research method that aims to analyze the problems that are carried out by combining legal materials (which are secondary data) with primary data obtained in the field. From research at the BPOM office, the authors found that there are still many unlicensed cosmetics business actors who commit fraudulent acts in producing cosmetics without a distribution permit with chemicals obtained at low prices without thinking about the impact on the consumers who use them, which causes BPOM's losses. obstacles in distribution monitoring. Illegal cosmetics due to lack of control over goods entering the city area, especially the city of Gorontalo, lack of public knowledge to distinguish genuine cosmetics from fakes, so that the circulation of illegal cosmetics is rampant. In general, people are only interested in cheap prices without being keen to know the basic ingredients for making these cosmetics, cosmetic ingredients that are easily and cheaply found on the market and counterfeiters' knowledge about the composition of counterfeit cosmetics are the contributing factors. Illegal distribution of cosmetics.